2015
DOI: 10.2337/dc15-1037
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Week Treatment With Liraglutide as Add-on to Insulin in Normal-Weight Patients With Poorly Controlled Type 1 Diabetes: A Randomized, Placebo-Controlled, Double-Blind Parallel Study

Abstract: OBJECTIVEThis study investigated the efficacy and safety of once-daily liraglutide 1.2 mg versus placebo as add-on to insulin treatment in normal-weight patients with poorly controlled type 1 diabetes. RESEARCH DESIGN AND METHODSIn a randomized (1:1), double-blind, placebo-controlled design, 40 patients with type 1 diabetes (HbA 1c ‡8% [64 mmol/mol]) received once-daily liraglutide 1.2 mg or placebo for 12 weeks. Continuous glucose monitoring was performed before and at the end of treatment. The primary end po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
95
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 43 publications
14
95
1
1
Order By: Relevance
“…The current trial shows that these beneficial findings come at the expense of a higher rate of symptomatic hypoglycemia and more episodes of hyperglycemia with ketosis compared with insulin treatment alone. This finding has not been consistently reported before in people with type 1 diabetes when liraglutide was added to therapy, possibly reflecting the glycemic control and lower insulin dose in liraglutide-treated subjects, as well as difficulties in accurately adjusting bolus insulin and food intake (6,9). A more flexible insulin titration may have mitigated the risk of hypoglycemia, though this would have to be balanced with the constraints of the treat-to-target design required for wider risk-benefit analysis.…”
Section: Mmol/mol])mentioning
confidence: 64%
See 1 more Smart Citation
“…The current trial shows that these beneficial findings come at the expense of a higher rate of symptomatic hypoglycemia and more episodes of hyperglycemia with ketosis compared with insulin treatment alone. This finding has not been consistently reported before in people with type 1 diabetes when liraglutide was added to therapy, possibly reflecting the glycemic control and lower insulin dose in liraglutide-treated subjects, as well as difficulties in accurately adjusting bolus insulin and food intake (6,9). A more flexible insulin titration may have mitigated the risk of hypoglycemia, though this would have to be balanced with the constraints of the treat-to-target design required for wider risk-benefit analysis.…”
Section: Mmol/mol])mentioning
confidence: 64%
“…The administration of liraglutide as an adjunct to insulin has consistently shown a reduction in daily insulin dose and weight loss compared with control subjects, and neutral or positive results in terms of HbA 1c levels and rates of hypoglycemia (6)(7)(8)(9)(10)(11)(12). This study aims to address whether adding liraglutide to insulin therapy in a treat-to-target approach can safely improve glycemic control in a population that is generally representative of people with type 1 diabetes when studied in a randomized, double-blind fashion over a 52-week period.…”
mentioning
confidence: 99%
“…A recent 12-week randomized study in normal-weight patients with T1D with 1.2 mg liraglutide and a 24-week randomized study from the same group in overweight and obese patients with poorly controlled T1D with 1.8 mg liraglutide demonstrated significant reduction in body weight and insulin dose without any additional effect on HbA 1c compared with placebo (14,15). The latter study also demonstrated reduction in hypoglycemic events (15).…”
Section: Discussionmentioning
confidence: 99%
“…Glucagon‐like peptide‐1 (GLP‐1) receptor agonists (GLP‐1RA) are of interest because of the ability of GLP‐1 to reduce glucagon secretion and delay the gastric emptying (GE) rate . Recently, we and others have provided evidence that GLP‐1RA treatment induces weight loss and reduces insulin requirements with unaltered or improved glycaemic control in persons with T1D . Additionally, in persons with T1D, liraglutide has been shown to suppress postprandial glucagon secretion after 12 weeks of treatment …”
Section: Introductionmentioning
confidence: 99%